An analysis of migration and implications for health in government policy of South Africa - Karima Manji; Shehani Perera; Johanna Hanefeld; Jo Vearey; Jill Olivier; Lucy Gilson; Helen Walls (BMC, 2023)
Abstract For over a decade, the global health community has advanced policy engagement with migration and health, as reflected in multiple global-led initiatives. These initiatives have called on governments to provide universal health coverage to all people, regardless of their migratory and/or legal status. South Africa is a middle-income country that experiences high levels of cross-border and internal migration, with the right to health enshrined in its Constitution. A National Health Insurance Bill also commits the South African public health system to universal health coverage, including for migrant and mobile groups. We conducted a study of government policy documents (from the health sector and other sectors) that in our view should be relevant to issues of migration and health, at national and subnational levels in South Africa. We did so to explore how migration is framed by key government decision makers, and to understand whether positions present in the documents support a migrant-aware and migrant-inclusive approach, in line with South Africa's policy commitments. This study was conducted between 2019 and 2021, and included analysis of 227 documents, from 2002-2019. Fewer than half the documents identified (101) engaged directly with migration as an issue, indicating a lack of prioritisation in the policy discourse. Across these documents, we found that the language or discourse across government levels and sectors focused mainly on the potential negative aspects of migration, including in policies that explicitly refer to health. The discourse often emphasised the prevalence of cross-border migration and diseases, the relationship between immigration and security risks, and the burden of migration on health systems and other government resources. These positions attribute blame to migrant groups, potentially fuelling nationalist and anti-migrant sentiment and largely obscuring the issue of internal mobility, all of which could also undermine the constructive engagement necessary to support effective responses to migration and health. We provide suggestions on how to advance engagement with issues of migration and health in order for South Africa and countries of a similar context in regard to migration to meet the goal of inclusion and equity for migrant and mobile groups.